DIRECT FEEDBACK STRATEGY IN THE TEACHING OF WRITING (RETAIN, 2014)
DIRECT FEEDBACK STRATEGY IN THE TEACHING OF WRITING Army Vista Casmi Septianik English Education Department, Language and Art Faculty, Surabaya State University. email: armyvistacs@yahoo.co.id Prof. Dr. Susanto, M.Pd. English Education Department, Language and Art Faculty, Surabaya State University. Abstrak Penelitianinibertujuanuntukmendiskripsikanpenerapanstrategi Direct Feedback oleh guru untukmengajarmenulispadasiswakelassepuluh di sekolahmenengahatas Surabaya.Dalam proses pengajaranmenulisini guru menggunakanempattahapdalampenerapanstrategi Direct Feedback. Merekaadalahtahapperencanaan, penyusunan, pengeditan, danhasilakhirterbaru.Padatahapperencanaan, guru memberikanpenjelasandanpengungkapanpendapattentangapa yang akan di lakukandalampelajaranmenuliskepadasiswa. Setelahitu guru memintakepadasiswauntukmerencanakandanmenuliskan ide secarabebas yang berkaitandengan topic teks recount dalampengajaranmenulis. Dalamtahap yang keduayaitupenyusunan, guru memintakepadasiswauntukmengembangkan ide merekakedalamsuatuparagraf.Kemudiansetelahsiswaselesaimengembangkan ide dalamparagraf, guru memintasiswauntukmengkoreksikembalitulisanmerekadengancaradikoreksiolehtemansebangku. Tahap yang ketigaadalahtahapdalampengeditan.Dalamtahapini guru memberikanpengkoreksiandarihasiltulisansiswasetelahmendapatkanpengkoreksianolehtemansebangkudenganmenggunakan Direct Feedback strategibaiksecaralisanatautulisan.Yang teakhiradalahtahaphasilakhirterbaru.Dalamtahapini guru memintasiswauntukmengumpulkanhasilakhirtulisanmerekasetelahmendapatkankoreksidaritemansebangkudan Direct Feedback dari guru dalampertemuanberikutnya. Penelitimenggunakandeskriptifkualitatifdalamdesainpenelitian, karenatujuandaripenelitianiniadalahuntukmenggambarkankegiatan guru selamapelaksanaan Direct Feefbackstrategidalampengajaranmenulis.Penelitihanyamemilihpadasalahsatu guru bahasainggris yang mengajar di sekolahmenengahatas di salahsatukota di Surabaya. Data dalampenelitianinidiperolehdarihasilobservasi yang menggambarkanpenerapan Direct Feedback strategidalambentukpengkoreksiantulisansiswa.Data di analisisuntukmenjawabsemuapertanyaanpenelitian.Penulismenulissemuainformasitentangsegalasesuatu yang terjadiselama proses kegiatanbelajarmengajardalambentukcatatan yang panjang. Hasildanpembahasanadalah, pertamaadalahtahappenerapan Direct Feedback strategihanyaterfokusdalam proses kegiatanbelajarmengajar. Dalamtahapinipenerapan Direct Feedback dibagimenjadiempattahapanyaitutahapperencanaan, penyusunan, pengeditan, danhasilakhirterbaru.Dalampemberian feedback guru menggunakanempatperandalam proses iniyaitu guru sebagaipembacaataupartisipasi, sebagai guru menulisataupenuntun, sebagaiahlitatabahasa, dansebagaipengkoreksi. Dalamtahap yang keduaadalahtahappenerapan Direct Feedback strategiuntukmengkoreksitulisansiswadalambentukkesalahantatabahasa.Dalamsesiini, guru masukdalamtahappengeditandanmelakukanperannyasebagaiahlitatabahasa.Yang ketigaadalahtahappenerapan Direct Feedback strategiuntukmengkoreksitulisansiswadalambentukperbendaharaan kata.Dalamsesiini, guru masukdalamtahappengeditandanmelakukanperannyasebagaipengkoreksi.Padatahapankeempatatauterakhiradalahtahappenerapan Direct Feedback strategiuntukmengkoreksitulisansiswadalambentukpenggunaanparagrafing, pengejaan kata dan capitalization.Dalamsesiini, guru masukdalamtahappengeditandanmelakukanperannyasebagaipengkoreksi. Dari hasil proses kegiatanbelajarmengajarmenulistersebut, penulisdapatmenarikkesimpulanbahwa Direct Feedback strategisesuaiuntuksiswadalamkegiatanbelajarmengajarmenuliskarenadenganstrategiitu guru dapatmembantukesulitansiswasepertimembantumengurangikesalahansiswadalamkegiatanmenulis. Saran bagi guru adalahuntuklebihsadardalampenggunaanwaktudanbagipeneliti lain dapatmelakukanpenelitianserupadalamaspek lain danbisamenggunakanpenambahanpemberian feedback dalamkategorikontendanorganisation. Kata Kunci: Direct Feedbcak, Strategi, KegiatanMenulis. Abstract This study aims to describe the application of the strategy of Direct Feedback by teachers to teach writing to the students in the tenth grade of high school in Surabaya. In the process of teaching writing the teacher uses four stages in the implementation of Direct Feedback strategy. They are planning, drafting , editing , and the latest final versions. In the planning stage, the teacher gives an explanation and brainstorming to the students regarding what they are going to do in writing lessons. After that, the teacher asked the students to plan and write their ideas freely that are related to the topic in teaching writing of recount text. In the second stage, is drafting activity. Here the teacher asked the students to develop their ideas into a paragraph. Then, after the students finished developing their idea into a paragraph, the teacher asked the students to re- writing their work by using peer correction. The third stage is editing. In this stage the teacher gave the students' correction of their work after getting friends correction inpeer correction with the Direct Feedbackstrategy either in orally or in writing. For the last stage is final version. In this stage, the teacher asked the students to submit their final product after getting corrections from their friends and Direct Feedback from the teacherin the next meeting. The researcher used a descriptive qualitative research design, because the purpose of this study is to describe the activities of the teacher during the implementation of the Direct Feefback strategies in teaching of writing. The researcher chooses the one of English teacher who teachesin high school in one of the cities in Surabaya. The data in this study weretaken from the observation that illustrates the application of direct feedback correction strategy in the form of student writing. The data were analyzed descriptively to answer the research questions. The writerwrote all the information about everything that happened during the teaching and learning process in the form of long notes. The results and discussion are, in the first stage of the implementation ofDirect Feedback strategy is only focused in the process of teaching and learning activities. In the implementation of Direct feedback is divided into four stages, they are planning, drafting, editing, and the last final version. In providing feedback the teacher use four roles in this process, they are the teacher as reader or participation, as teacher writing or guide, as a grammarian, and as a evaluator. In the second stage is the implementation stage of the Direct Feedback strategies for correcting students' writing in the form of grammatical errors. In this term the teacher in editing stage and she act her role as grammarian. The third is the implementation stage of the Direct Feedback strategies for correcting students' writing in the form of vocabulary. In this stage the teacher in editing stage and she act her role as evaluator. In the fourth and final stage is the implementation stage of the Direct Feedback strategies for correcting students' writing in the form paragrafing usage , spelling words and capitalization. In this stage the teacher in editing stage and she act her role as evaluator. From those results of the process of teaching-learning in writing, the writercan draw the conclusion that Direct Feedback strategy is appropriate for the of students in learning activities because the teacher can help the student’s difficulties such as helping to decrease the students’mistakes in their essays. Suggestions are to the teacher and other researchers. For the teacher has aware to time and for other researchers who will conduct this similar studies but in other aspects they can use the additional corrections of feedback on the content and organization categories. Keywords: Direct Feedback, Strategy, Writing Activities. Introduction In Merrill’s Component Display Theory verifies feedback as the most important part in Secondary Presentation feedback may takes place during practice and/or elaboration stages. (Merrill 2002) states that feedback has also been long acknowledged as the most essential form of learner guidance. To confirm further of the important position of feedback, Andrews and Goodson (1980) state that feedback is included in one of the purposes of systematic instructional design that is to improve evaluation process “by means of the designated components and sequence of events, including feedback and revision events, inherent in models of systematic instructional design”. In this case, feedback as strategy applied by the teacher is the important position to improve the students evaluation or when teaching learning process during practice and revisions in class. Feedback is also an important component of the formative assessment process. Here, formative assessment gives information to teachers and students about how students’ writing relate to classroom learning goals. One of the strategies use by the teacher in giving formative assessment is by using direct feedback. Direct feedback is a strategy which provides feedback to students to help them correct their errors by providing the correct linguistic form or linguistic structure of the target language (Ferris, 2006). This technique requires the teacher to give direct comment or answer to the student when noticing a grammatical mistake made by crossing out an incorrect or unnecessary word, phrase, or morpheme; inserting a missing or expected word, phrase, or morpheme; and by providing the correct linguistic form above or near the erroneous (Ellis, 2008 ; Ferris, 2006). Bitchener et al., (2005) and Ferris (2003) add that Direct feedback is usually given by teachers, upon noticing a grammatical mistake, by providing the correct answer or the expected response above or the linguistic or grammatical error. From those statements, direct feedback can be used by the teacher to help the students’ difficulties such as using appropriate, accurate and complete responses, correct spelling and punctuation, ensuring minimum word limit, grammatical accuracy, range of sentence structure, and range of vocabulary in writing activity. Direct feedback as a strategy is appropriate for students in beginner level or in situation when the students get errors in their works that are not easy to do self-correction such as sentence structure and word choice, or it can be useful when the teachers want to direct the student attention to their error patterns that require the student correction. The effectiveness of direct correction has been proven on several previous studies. Chandler (2003) reported the results of her study involving 31 ESL students on the effects of direct and indirect feedback strategies on students’ revisions. She found that direct feedback was the best way for producing accurate revisions and preferred by the students as it was the fastest and the easiest way for them to make revisions. Others, the most recent study on the effects of direct corrective feedback involving 52 ESL students in New Zealand was conducted by Bitchener and Knoch (2010) where they compared three different types of direct feedback (direct corrective feedback, written, and oral metalinguistic explanation; direct corrective feedback and written metalinguistic explanation; direct corrective feedback only) with a control group. They found that each treatment group outperformed the control group and there was no significant difference in effectiveness among the variations of direct feedback in the treatment groups. From the above statements, it can be concluded that direct feedback is effective to be used in teaching writing. Although direct feedback is effective to be used, there is a difficulty when the teacher uses it in large class environment. The teacher needs much time to give feedback to the students. Clements et al. (2010) state that direct methods in providing feedback do not tend to have results which are commensurate with the effort needed from the teachers to draw the students’ attention to surface errors. From the information above it can happen because the teacher doesn’t give students an opportunity to think or to do anything. Therefore to overcome the above problem, the teacher needs to understand the writing steps to avoid time-consuming. Writing should be taught in a specific time in order to enable the students to write an acceptable English composition. Then, in teaching writing, the teacher can focus either on the product of writing or on the writing process itself (Harmer, 2001:257). It means that, the teacher can manage the students written by using three steps before teaching writing because by doing that the teacher can more focus on the product or the process of writing itself. Here there are three steps in writing, they are: In the pre-writing, whilst-writing, and post-writing. In the pre-writing, the teacher asks the students to: select the topic, provide specific amount of time needed to complete their writing task, brainstorm their ideas, and organize their outline. In the whilst-writing, the teacher asks the students to make draft and ask them to submit their work when they finish. In post-writing, the teacher gives the students revision regarding their work. By understanding the preceding steps, the teacher can manage the time during teaching learning activity. In one of the school in Surabaya, there is a teacher who use direct feedback strategy to teach writing. In her result, she finds advantages by using direct feedback as a strategy to teach writing, such as the students get creative, enjoy, and enthusiastic. By this method, the students become creative it is showed when the teacher revises the student’s work. The teacher finds that the students frequent to use new words. Moreover, the students feel enjoy when the teacher revise their work without looked nervous. The last, the students are eager to ask and re-write their revision. Although there are several advantages, the teacher does not give further explanation how to use the technique in teaching learning activity. Brookhart (2008) states that giving feedback is crucial aspect in the writing process because it plays a central role in learning this skill. Thus, from the information above, the researcher is interested to conduct research about the use direct feedback strategy to teach writing. From the information above, the most three problematic grammatical errors made by the students are prepositions, text, and past tense verbs (Bitchener et al., 2005; Ellis et al., 2008; Sheen, 2007). Most of the student’s mistakes in writing is about grammar. It is the teacher role to use strategy in direct feedback because it will be useful to use it to reduce or help the students’ mistakes in writing skill. One topic about student’ views toward the teacher feedback on their written errors showed in studies: Chenowith, Day, Chun, &Luppescu (1983); Cohen (1987); Cohen &Cavalcanti (1990); Ferris (1995); Ferris & Roberts (2001); Ferris et al. (2000); Hedgcock&Lefkowitz (1994); Komura (1999); Leki (1991 ); Radecki& Swales (1988); and Rennie (2000). It has consistently reported that students want such error feedback. This is the teacher's advantages, because most of students want such error feedback from the teacher. The teacher can give the students’ stages of process writing feedback in revising and editing stages. According to Ferris and Roberts (2001), the most popular type of feedback is underlining with description, followed by direct correction, and underlining is the third. That’s kinds of ways make the teacher to get much attention from the students in applying direct feedback strategy in teaching of writing. The phenomena shows that most teachers prefer focus on the product of writing to focus on the process of writing. As a result, the competition that the students write is poor in terms of the overall categories in ESL Composition Profile including content, organization, vocabulary, language use, and mechanics. It occurs since the teacher does not provide guidance through the process of writing and considers writing as a finished piece of competition. In fact, writing is not only the matter of composition as a finished piece of writing, but also the evaluation of the writing process. Therefore, in order to enable the students to write an acceptable English composition, the teacher has better focus on the process approach in which the process of writing is involved. Process approach is considered as the appropriate method to teach writing in which it pays serious attention to the various activities which are believed to promote the development of skilled language use (Nunan, 1991:86). Furthermore, Raimes in Richars (2005:305-509), in principled process approach, the product of writing, accuracy, and grammar are important. It shows that if the teacher focuses on the process of writing when he or she teaches writing, it does not mean that he or she merely focuses on the writing process itself, but also on the quality of the final product. Therefore, the process of writing is considered as the appropriate method to teach writing since it enables the students to write an acceptable English competition. From those, the researcher tends interested to observe this phenomenon by emerging a question that is “to what extent does the teacher apply direct feedback in writing?” The researcher was trying to analyze the activities during the teaching and learning process that using Direct Feedback as strategy. According to those reasons the researcher did a research according to the following research questions To what extent does the teacher apply direct feedback to correct student’s grammatical errors in writing? To what extent does the teacher apply direct feedback to correct student’s vocabularies in writing? To what extent does the teacher apply direct feedback to correct student’s mechanics in writing? This study is conducted to describe only focused on the implementation of Direct Feedback strategy in teaching of writing. Writing is a part of learning process besides listening, speaking, and reading. According to Petty and Jensen (1980:399) writing is an activity that creates ideas or opinions in a composition by using writing convention: it is ideas though, feeling expressed in written way. This is in line with Nunan (2003:88) views that writing is the mental work of inventing ideas, thinking about how to express them into statements and paragraphs that will be clear to the reader. It means that writing is combination of some words to deliver the ideas in written language. Besides that, writing is also a language skill that is used to communicate indirectly. It means that the written language is not used to communicate face to face. According to Broughton et al (1980), writing is different from speaking because it involves an activity that is both private and public. here it means writing is considered a private activity because when the writer write or arrange a composition, he or she works individually, but it is also considered as a public activity because the result of his or her writing is intended for an audience. Others, according to Boughy (1997), writing is considered as a tool for the creation of ideas and the merger of the linguistic system by using it for communicative objectives in an interactive way. From this opinion writing indirectly the successful transmission of ideas from a writer to a reader via text and this exchange of information becomes an effective means to motivate and encourage the development of the students in language skills. Harmer (2007: 325-327) stated that there are four stages in the writing process: they are planning, drafting, editing, and final version. In this study the researcher will use Harmer’ concept: Planning In the planning stage the teacher arranges the students to plan their work before making a draft by exploring the ideas and information regarding the topic. Reading and discussing, thinking critically and interpreting, and brainstorming are examples of exploring. Boas (2011) says that planning stage is used for brainstorming ideas which are related to their lives and what they want to write.Moreover, in planning the teacher encourage the students to make an outline that includes thesis statement and supporting ideas which then are developed into an essay. Drafting The second stage is draftingwhere the students develop the outline into a whole essay. In this stage, the teacher asks the students to write anything on their mind to compose the essay in form of the rough draft without thinking the regularity of their writing. Editing The third stage is editing, where the students revise their rough draft. In editing, the teacher encourages the students to revise their draft by considering several aspects, such as: the relevancy between thesis statement and the topic, the topic paragraph should be used in beginning of the paragraph, and the content should relate with the thesis statement. Or also the students can check the content, grammar, vocabulary, mechanics, and so on.Moreover, producing a cohesive another coherent essay is a must and can only be done by enlarging the argument or opinion, and ideas to make an elaborate explanation that is coherent from one to another. Final Version The last one is final version, where the teacher asks the students to compose their draft carefully, find, and edit their grammatical, lexical, and mechanical errors before submitting their work. In this stage, the teacher must ensure the students that their final works are free from previous errors since it can affect the content of their final product. But the students still have chance to rethink what they have written and go back to editing stage or even planning stage. Like Harmer (2012:129) states that writing stages are like writing cycle, if it is necessary to add ideas or edit their writing, we can go back to the previous stage or stages. But if it does not need to edit, the students can do their writing final version. Feedback can be classified according to the following: The performer (the provider) of feedback (teacher, peer, self and CALL Computer Assisted Language Learning), the timing of feedback (delayed and immediate feedback) and the form of feedback (direct and indirect feedback), the method of performance of feedback (oral and written feedback), the concentration on a specific item in feedback (grammar, spelling and etc.), the stage of process writing feedback and the effect of feedback (feedback in revising, editing stages). The purpose of this study will be explained to two types of the teacher’s written feedback. Here the types, they are: Direct and Indirect feedback. The first type of the teacher’s written feedback is direct feedback. Danny and Randolph & Karen (2010) Altena& Pica (2010) Direct teacher feedback simply means that the teacher provides the students with the correct form of their errors or mistakes whether this feedback is provided orally or written. It shows them what is wrong and how it should be written, but it is clear that it leaves no work for them to do and chance for them to think what the errors and the mistakes are. The second type of the teacher’s written feedback is indirect feedback. In this type, there are two types of feedback coded indirect feedback and uncoded indirect feedback. As for the first type “coded indirect feedback”, the teacher underlines the errors or mistakes for the students and then the teacher writes the symbol above the targeted error or mistake and then the teacher gives the composition to the student to think what the error is as this symbol helps the student to think. In the second type, the uncoded indirect feedback, the teacher underlines or circles the error or the mistake and the teacher doesn’t write the correct answer or any symbols and the student thinks what the error is and corrects. Teacher is one of the sources of feedback. In providing feedback, writing teachers have at least four roles: as a reader or respondent, as a writing teacher or guide, as a grammarian, and as an evaluator. As Keh (1990) and Hedgcock and Leftkowitz (1996) suggest at least four roles that writing teachers play while providing written feedback to students: a reader or respondent, a writing teacher or guide, a grammarian, and an evaluator or judge. For the first roles, is about the teacher as a reader or as a respondent. In this role, the teachers respond to the content and they may show agreement about an idea or content of the text. Teachers may provide positive feedback such as “You made a good point” or “I agree with you” without giving any suggestion or correction. The second is the teacher as a writing teacher or as a guide. That is, teachers may show their concern about certain points or confusing or illogical ideas in students’ text. In this case, teachers still maintain their role as a reader by only asking for clarification or expressing concerns and questions about certain points in the text without giving any correction. They may, however, refer students to strategies for revision such as choices of problem solving or providing a possible example. The third is the teacher as a grammarian. The teacher writes comments or corrective feedback with reference to grammatical mistakes and relevant grammatical rules. Teachers may provide a reason as to why a particular grammatical form is not correct or not suitable for a certain context such as choice of tense, use of article, or preposition. In this case, the teacher may also give elaborate explanation of grammatical rules to help students improve their text. As a grammarian, teacher can provide different function and strategies of feedback. One of the functions of feedback is to provide error correction or corrective feedback. Corrective feedback generally aims at addressing grammatical errors on students’ writing. In addressing grammatical errors on students’ writing, teachers can employ different strategies of providing feedback such as direct feedback strategy. Direct feedback, which is a strategy to help the students correct their errors by providing the correct form of the target language. Teacher feedback can also be provided with explicit corrective comments, that is by not only indicating an error but also providing the correct form with explicit grammatical explanation or linguistic rules of the target language. The last in fourth roles, is the teacher as an evaluator or judge. It is very common that many writing teachers may act only as an evaluator whose main role is to evaluate the quality of students’ writing as an end product of a writing process (Arndt, 1992) and grade students’ writing based on their evaluation. Discrepancies in findings, or in interpreting these findings, have sparked a debate in the last 15 years on whether corrective feedback is effective or ineffective. The debate was initiated by Truscott (1996) who unalterably holds that feedback, in the form of grammatical error correction, is neither effective nor useful, and even harmful for student learning. Therefore, he suggests that corrective feedback should be abandoned. In contrary, Chandler (2003) and Ferris (1999) argue that corrective feedback is effective and helpful in reducing the errors on students’ essays. More recent studies also lend support, providing evidence in favor of corrective feedback Bitchener (2008); Bitchener et al. (2005);Ellis et al. (2008). Based on the findings of their studies, they maintain that teacher corrective feedback is effective and helpful for students in improving grammatical accuracy in writing their essays. From the above informations, it can be concluded that direct feedback is effective to be used in teaching writing. Teaching writing using direct feedback is considered as an important since it gave the teacher chances to increase the students ability in writing by using learned-centered style. Since previous statements have considered that learned-centered style in form of peer or group work is preferred than compositions because it offers interaction and sharing ideas between students. However, before implementing the strategy the teacher should make the process steps before starting applying direct feedback as strategy in teaching writing. The implementation of Direct Feedback strategy in teaching writing recount text should include writing process; they are planning, drafting, editing, and final version Harmer (2007: 325-327). Based on those concept, the implementation of Direct Feedback strategy in teaching writing recount text in the class have some activities to do. They are: The teacher explains the nature of recount text, it start from the purpose, the function, the generic structure, and the language features to the students by some modification by using brandstorming or etc. The teacher also gives example of recount text to the students in order to make the students understand with the teacher’s explanation and example of how to make mind mapping. The teacher gives the students some topics to write recount text. The teacher asks the students to make such like mind mapping as the planning stage. The students make mind mapping to write down their ideas they want to write it individually. After the students make mind mapping on their recount text, the teacher asks them to exchange their work in pairs. They can give comments, questions, suggestions, and corrections about the content, organization, vocabulary, language use, and mechanic on their partner mind mapping to compose into recount text draft. Then each student can write their recount text draft based on their friend questions, suggestions, comments, and corrections. The next activity is sharing. In this case, the teacher calls some students randomly one by oneto come forward to show their recount text by writing their text into white board. Therefore, the other students get patient too and also learn which one is not appropriate word, the mechanics, or the content by giving comments orsuggestions. And the most necessary, the teacher givesDirect Feedback to their recount text. Teacher gives direct feedback by giving explicit corrective comments, symbols, or underlining. Ellis et al. (2006) suggest that explicit corrective comments can take two forms: (a) explicit correction in which teacher response clearly indicates what is incorrect and provides the correct form, or (b) metalinguistic feedback which explains grammatical or linguistic rules. Lyster and Ranta (1997) define metalinguistic feedback as “comments, information, or questions related to the well-formedness of the learner’s utterance without explicitly providing the correct form” (p. 47). Finally, the students submit their recount text result as the final version to the teacher on the next meeting. METHODS Based on the research problems and the objective of the study, the researcher used descriptive qualitative method. Descriptive qualitative studies simply describe phenomena. Descriptive method describes and interprets what exists.The purpose of this study is to describe to what extent the teacher applies direct feedback to correct student’s grammatical errors in writing, to describe to what extent the teacher applies direct feedback to correct student’s vocabularies in writing, and to describe to what extent the teacher applies direct feedback to correct student’s mechanics in writing. According to Cohen, et al (2007:461), the aims of descriptive qualitative are to describe, to summarize, to prove, to examine the application and to operate the same problems in different contexts. The purpose of this study is to describe the teaching learning process in the form of words not in the form of numbers, because this study is descriptive qualitative. Moreover, Bogdan and Biklen (1992:28) state that the data collected should be in the form of words or pictures rather than numbers. The data in this study described in the form of words, sentences, or paragraphs to describe the implementation, the students’ responses, and the students recount writing text result using Direct Feedback strategy in teaching writing recount text.Descriptive qualitative method means that the researcher only goes to the field, finds some data, states research question, collect some data, analyze the data and finally reports it. The data is the problem which is found in the field. The problem means that the condition found in the field is not like the condition expected. The subject of the study is an English teacher who teach in a high school of Surabaya. The researcher chose the subject because one of the teachers had implemented Direct Feedback method in the teaching writing in her class.Cohen, et al (2007:461) states that descriptive qualitative focuses on smaller numbers of people than quantitative research.Therefore, the researcher only chooses an English teacher who teaches English in X-IPA 10 class. The setting of the study was the place where the researcher conducted the study. The researcher was conducting the study at SMAN 15 Surabaya which is located in Jl. Menanggal selatan no. 103 Surabaya, the class of X-IPA-10 year 2013 and 2014. These class consist of 36 students, 16males and 20females. This research conducted in the classroom where the teacher hadusedDirect Feedback strategy in teaching writing recount text. Furthermore, the classroom is provide by facilities which support the learning activivities, such as White board, LCD, AC, Computer, sound, television and a laptop. The students have arranged the chairs and tables well in order to make them study easily. Data is very important for this study because from by using data the researcher knew the result of her study through this data, and the data were answer the research questions. In this study the researcher do not use questionnaire, it is to avoid dishonesty and to anticipate that the subjects would not complete the questions. The data of the study taken from the teaching learning process that done by the teacher who using direct feedback as strategy in teaching writing in the classroom. To get the data, the researcher wrote field notes to observe the teacher’s activities when giving direct feedback in the teaching and learning process. The data represented in the post activity of the teacher when giving the students direct feedback while learning in the classroom. There were three kinds of qualitative data to answer the research questions of this study. The first data were the description of teachers’ expressions and comments while giving correction about grammatical errors and direct feedback to the students. (1) (1) Teacher : Teacher : Okay, I will check the Savira’s text. By the way, for the grammatical errors she did some mistakes. For example: in the first paragraph line 1 “I had a terrible and tiring day last weekend”, here (a) it should be omitted. In paragraph one Line 2 “In the morning, I was waking up at 5 a.m. and prayedsubuh”, if in the beginning you use waking as a verb so second verb prayed should be using (–ing) to. So it should be praying. Next, in line 5 “we must joined” it should be write “join”, because must be followed by Verb1. Last, in line 11 you wrote “my other key” it should be used “the”. Next, for Afanin’s text. Okay you did same with Safira’s text in grammatical errors. For example: you wrote “after that, me and my mother cooked some food for lunch”, it should be used we. Then for the sentence “I went to bookstore to boughtsome book”, it should be buy because you have use went as your verb. Last for “I do my homework” it should be written did. These data were used to answer the first research question “to what extent does the teacher apply direct feedback to correct student’s grammatical errors in writing?”. The second data were the description of teachers’ expressions and comments while giving correction about vocabularies and direct feedback to the students. (2) (2) Teacher : Teacher : And for vocabulary, it just for the first paragraph line 3 “I accompanied my mother (..)to shop” between my mother and to it should be add “go”. For the last paragraph, “InSunday morning” remembers it should be on just like Ataya did before. But, so far I think your word choices were good. And talk about “like yesterday” I think it should be wrote the day before. This is correction for your vocabulary. It is also in sentence “I accompanied my mother to (..) the market” here it should be add go to, and also like we went (..) to the mall” it should be added go. These data were used to answer the second research question “to what extent does the teacher apply direct feedback to correct student’s vocabularies in writing?”. The third data were the description of teachers’ expressions and comments while giving correction about mechanics and direct feedback to the students. (3) (3) Teacher : Teacher : So the last correction is about mechanics. It showed in line 16 “I was watching television” it should be added (a) between watching and television. “I was watching a television”. Over all your writing are good Safira. So keeps on this track but you can explore more. Okay, that’s very good. Okay then, pay attention to the mention things like “some vegetables, like carrot , tomato, spinach , onion , garlic , ginger , curcuma, and many more and also bought some fish, shrimp, and chicken.”Here you have decided space from kind of vegetables itself and others thing. You should write some vegetables, they are likes carrot, tomato, spinach, onion, garlic, ginger, curcuma, etc. We also bought more, such as fish, shrimp, and chicken. And for your mechanics, there are lot mistakes about your punctuation. Such like in the first paragraph “last weekend ( , ) I had a lot of activities”. You used comma but you add space after weekend, it should be not space after weekend. Double space is not necessary guys. So the good one is like last weekend, I had a…. Okay, for your right spelling and capitalization are good, but please pay attention about your punctuation and your paragraphing..yah? Is it clear for you guys? These data were used to answer the third research question “to what extent does the teacher apply direct feedback to correct student’s mechanics in writing?”. The source of data for this study was the teacher who use direct feedback strategy to correct the students mistakes in the teaching and learning process. Data collection technique means how the researcher collects data. In this study the researcher collected the data by conducting observation field notes as a qualitative. Bogdan and Biklen in Moleong (2005: 209) stated field note is written note about what was heard, seen, thought and had been around in order to collect as well as reflect the data in qualitative research. Here, the researcher done non-participant observation. It means that she does not participate directly and influence in the teaching and learning process. The writer wrote all of information about everything that happening during the teaching and learning process in the form of long note. Here is the observation that was done by the teacher: Observation, in this research the researcher used observation field notes. She used this observation because she wanted to find out the application of the teaching and learning process in the classroom of their recount writing. The researcher did this observation by writing and record all of the activities of the teacher and the students while direct feedback is implemented. In this research, all the data obtained through observation field notes were analyzed inductively in order to answer research questions stated in chapter one. After collecting the data then the researcher did the next step, that was analyzed the data. This is the qualitative study thus the data analyzed inductively, in words rather than in numbers. The steps of data analysis have done during the data collection technique: 1) Organized the data during the observation, and then decided what have to be reported. 2) After analyzing the data, the researcher described the data by classifying them into parts based on the problems of the study. 3) The researcher tried to make conclusion. They showed whether the use of direct feedback strategy was suitable or not with the theory. In addition, by analyzing the data obtained, the researcher was written and recorded the teacher activity when direct feedback strategy is applied in the classroom. It included the teacher correction about grammatical errors, vocabularies and mechanics. RESULT AND DISCUSSIONS The result and discussions is the answer of the problems based in introductions. The data were taken through the observation and only focused on the teacher activities during the implementation of Direct Feedback strategy in the teaching and learning process. The Implementation of Direct Feedback Strategy The data were obtained through the observation that was focused in the teachers’ activities during the implementation of direct feedback strategy in the teaching and learning process. The implementation of the research was done only in one meeting. The implementation of Direct Feedback strategy method was divided into four stages, they are planning, drafting, editing, and final version. Then in providing feedback, the teacher at least has four roles such as a reader or respondent, as a writing teacher or guide, as a grammarian, and as an evaluator. The observation was conducted on September 30th, 2013. The subject of the study is an English teacher who teaches in a high school of Surabaya. The researcher chose the subject because one of the teacher’s had implemented Direct Feedback method in the teaching writing in her class. Therefore, the researcher only chooses an English teacher who teaches English in X-IPA 10 class. Actually there were 36 students in this class, but three students were absent without any reason or information. Therefore, there were 33 students who consist of 16 male’s students and 20 female’s students in class X-IPA 10. The teacher started the class with opening session, for instance, greeting the students, checking the attendance list, and asking the students to prepare the lesson. The teacher did not introduced the researcher in front of the students, because of the teacher did not need the students to feeling nervous or uncomfortable if she explained about the researcher who want to record the activities in the beginning until the end of the lesson. The Applying of Direct Feedback Strategy to Correct Student’s Grammatical Errors in Writing The result from the observation show that the teacher had been explained the student mistakes’ about grammar. It showed when the teacher gives feedback with explicit corrective comments; she was not only indicating an error but also providing the correct form with explicit grammatical explanation or linguistic rules of the target language. As Ellis et al. (2006) suggest that explicit corrective comments can take two forms: (a) explicit correction in which teacher response clearly indicates what is incorrect and provides the correct form, or (b) metalinguistic feedback which explains grammatical or linguistic rules. So, here the teacher has applied direct feedback as strategy in writing to correct the student’s grammatical errors. In the previous studies that providing explicit corrective comments through explanation of grammatical rules or metalinguistic information is advantageous for students in the long run, that it raises students’ grammatical awareness, and engages students in problem-solving activities to discover the correct forms see Bitchener et al (2005), Ellis et al. (2006), Ferris &Hedgcock (2005), Nagata (1997), Varnosfadrani&Basturkmen (2009). The findings of the current study, in line with other previous studies, clearly indicate that teacher corrective feedback is useful and effective in helping ESL/EFL students in reducing their grammatical errors not only in subsequent revisions but also in the new essay. Furthermore, providing teacher corrective feedback in the form of indirect feedback followed by direct feedback accompanied with explicit corrective comments help students correct their grammatical errors more effectively than other feedback strategies, especially compared to direct feedback strategy. By doing so, the students got the essay way to edited or revised their works because they got some corrections and suggestions from their friends in pairs and from the teacher when the teacher gave them direct feedback. Jacobs et al (1997:20) says that the students can share to the other groups in front of the class and the students can edit their recount text writing depend on their friends comments, suggestions, corrections about the content, organization, vocabulary, language use, and mechanic in writing recount text. The Applying of Direct Feedback Strategy to Correct Student’s Vocabularies in Writing Based on the result which are gained from the analyzed of data,the teacher had took examples from Safira and Afanin Text’s. It showed that the teacher had corrected the students’ mistakes’ about vocabularies. In vocabulary component, those were two students who considered as write less mistakes in their writing text. As (Ellis, 2008; Ferris, 2006), stated that direct feedback may be done in various ways such as by striking out an incorrect or unnecessary word, phrase, or morpheme; inserting a missing or expected word, phrase, or morpheme; and by providing the correct linguistic form above or near the erroneous form, usually above it or in the margin. It means that, the teacher had correct the students’ mistakes by doing some ways to correct their vocabularies, such as by striking out an incorrect or unnecessary word, phrase, or morpheme; and inserting a missing or expected word, phrase, or morpheme. It is been shown when the teacher corrects Safira’s text. She corrected her mistakes by inserting a missing word. And from Afanin’s text, she gave by striking out an incorrect or unnecessary word like yesterday to be the day before. From the above correction, it is clear that the teacher applied direct feedback strategy to correct the students’ vocabularies by using that ways. So that is the essays way to encourage the students to get the motivation because the teacher not only giving them such corrective correction but they also know what else their mistakes by using self-correction in the next time. The Applying of Direct Feedback Strategy to Correct Student’s Mechanics in Writing In these criteria, the students had few errors of spelling, capitalization, and paragraphing. It means that the students were occasional errors of spelling, punctuation, capitalization, paragraphing but the meaning was not obscured. From the data analyzed indicate that the teacher correct the students’ mistakes in term of the mechanics. After the teacher giving those students text’s direct feedback correction, she always asked to the students any question or also suggestion. Based from those results which are gained from analysis of the data, the researcher concluded that the teacher did her implementation of direct feedback strategy method that was divided into four stages, they are planning, drafting, editing, and final version. Also in providing feedback, the teacher at least did her four roles such as a reader or respondent, as a writing teacher or guide, as a grammarian, and as anevaluator. From those, it can be concluded that the teacher had applied Direct Feedback to correct the student’s essays that includes three elements; they are grammatical errors, vocabularies, and mechanics. Ideally, the teacher feedback should address to all aspects of student texts such as content, ideas, organization, rhetorical structure, grammar, and mechanics. Because it will consume much time, so the teacher only focused to correct on the students grammatical errors, vocabularies and mechanics. It was supported by Ferris (2003b) notes that teachers’ priorities for student writing as well as feedback provision have changed over time from focusing mostly on sentence-level correction as reported in the 1980s Cumming (1985), Kassen (1988), Sommers (1982), Zamel (1985) to more aspects of student writing including ideas, organization, grammar, and mechanics in the 1990s Ferris (1995-1997), Ferris, Pezone, Tade, &Tinti (1997) Kepner (1991), Hedgcock&Lefkowitz (1994). However, providing comprehensive or unfocused feedback on all errors on students’ writing can be time-consuming and exhaustive for both teachers and students because it corrects all of the errors in students’ work and can be considered extensive Ellis, Sheen, Murakami, & Takashima (2008). By doing these strategy, the teacher had find out that most of the students were did mistakes in the grammatical errors. But, for the vocabularies and mechanics, the students did fewer mistakes in their essays. CONCLUSSION AND SUGGESTION Conclusion In this study, there are two conclusions got from the result of the study that are obtained from the observation, they are: (1) Direct feedback strategy can be used as teaching technique in teaching writing recount text to the tenth grade students of SMAN in Surabaya. The implementation of direct feedback as strategy in teaching writing of recount text divided into four stages, those are: Planning stage, in planning stage the teacher had given brainstorming and arranged the students to plan their work by exploring the ideas and information regarding to the topic. The teacher also had encouraging the students to make an outline that included thesis statement and supporting ideas which were developed into an essay. As Boas (2011) states that planning stage is used for brainstorming ideas which are related to their lives and what they want to write. Drafting stage, in drafting stage the teacher had asked the students to write their ideas into the essay in form of draft. This stage where the students developed the outline into a whole essay. Editing stage, in editing stage before the teacher gave direct feedback; she had corrected the student’s essay and let the students to change their works in pairs. Because in this term, the students had a chance to discuss and get comment or suggestion from their partner Jacobs et.al (1997:14). After that, the teacher applied direct feedback strategy by giving some correction from the student’s essay one by one in front of the class. Final version stage, in final version the teacher had given the students direct feedback and the students had shared their draft in front of the class. It included feedback from the teacher and from the students; comments or suggestions. Then the teacher let the students had to edit and submit the final version of their recount text on next meeting. (2) The use of Direct Feedback strategy could help the tenth grade students of SMAN in Surabaya in learning writing recount text. It showed from the editing stage, when the teacher applied Direct Feedback to correct the student’s essays in front of the class that includes three elements; they were grammatical errors, vocabularies, and mechanics, she found out that most of the students did the same mistakes. It came from the grammatical errors. For the vocabularies and mechanics, the students did fewer mistakes in their essays. The students also were getting enthusiastic when the teacher asked them to write a recount text based on the theme and their own experience, because the students could be more focus in writing recount text than usual (Kagan, 2004). As a result, direct feedback strategy was appropriate for the students in teaching and learning writing. Because the students usually got errors in their works and they were not easy to do self-correction such as sentence structure or word choice. From those, by using direct feedback the teacher could help the student’s difficulties such as using appropriate, accurate and complete responses, correct spelling and punctuation, ensuring minimum word limit, grammatical accuracy, range of sentence structure, and range of vocabulary in writing activity. And by using direct feedback the teacher could decreasing the students’ mistakes in writing activity. As noted by Cardelle and Corno (1981), the more feedback students receive, the better they understand what they need to do to correct their mistakes. It also prove by Kulhavy (1977) the understanding of why they make mistakes and how to correct such mistakes helps students correct their mistakes and increase their achievement. It means that the student who receives feedback would have information about which parts of their texts need to be corrected and improved. Carless (2006) confirms that students who receive feedback during the writing process have a clearer sense of how well they are performing and what they need to do to improve. As feedback is meant for helping students narrow or close the gap between their actual ability and the desired performance Brookhart (2003). Teachers are responsible for helping students develop their ability to reach their learning goals through teachers’ feedback. Suggestion Based on the data interpretation and the previous conclusion, the researcher has some suggestions to the teachers and the other researcher. The researcher constructs her suggestions as follows: (1) The teacher has to minimize the time consuming when she check the attendance the students. It means that the teacher should not call the student’s name one by one. (2) In the process of teaching, the teacher should know and understand the students’ characteristics. It means that the teacher does not give the students too much explaining or reminding them. (3) The researcher would like to invite next researchers who conduct the similar study to make improvement on this study, such as using the same field but different subjects. It means they can use the other subjects. (4) For the teacher and other researcher, the writer suggest to gives feedback for correct the content and organization. REFERENCES Arndt, V. (1992). Response to writing: Using feedback to inform the writing process. In M. N. Brock and L. Walters (Eds.), Teaching composition around the Pacific Rim: Politics andpedagogy (90-116). Avon, UK: Multingual Matters. Altena, l& Pica, T. (2010). The Relevance of Second Language Acquisition to Written Feedback on Advanced Second Language Writing. Unpublished PhD, University of Pennsylvania.3414220. Bitchener, J. (2008). Evidence in support of written corrective feedback. Journal of SecondLanguage Writing, 17, 102-118. Bitchener, J., & Knoch, U. (2009). The relative effectiveness of different types of directwritten corrective feedback. System, 37, 322-329. Bitchener, J., & Knoch, U. (2010). The Contribution of Written Corrective Feedback toLanguage Development: A Ten Month Investigation. Applied Linguistics, 31(2),193-214 Bitchener, J., Young, S., & Cameron, D. (2005). The effect of different types of correctivefeedback on ESL student writing. Journal of Second Language Writing, 14, 191-205. Carless, D. (2006). Differing perceptions in the feedback process. Studies in Higher Education, 31(2), 219-233. Chandler, J. (2003). The efficacy of various kinds of error feedback for improvement in theaccuracy and fluency of L2 student writing. Journal of Second Language Writing,12, 267-269. Cramer, S., et al. (2008). Online or Face-to-Face? Which Class to Take. Voices from the Middle, (2), 25. Elashri, I. I. (2013). The Impact of the Direct Teacher Feedback Strategy on the EFL Secondary Stage Students' Writing performance. Mesir: Mansoura University. Ellis, R., Sheen, Y., Murakami, M., & Takashima, H. (2008). The effects of focused andunfocused written corrective feedback in an English as a foreign language context.System, 36, 353-371. Ferris, D. (2003b). Responding to writing. In B. Kroll (Ed.), Exploring the dynamics of second language writing, (pp. 119-140). Cambridge, UK: Cambridge University Press. Ferris, D. R. (2004). The “Grammar Correction” debate in L2 writing: Where are we, and where do we go from here? (and what do we do in the meantime…?). Journal of SecondLanguage Writing, 13, 49-62. Ferris, D. (2006). Does error feedback help student writers? New evidence on the short- and long-term effects of written error correction. In K. Hyland and F. Hyland (Eds.), Feedback in second language writing: Context and issues (pp. 81-104). Cambridge, UK: Cambridge University Press. Ferris, D. R., & Hedgcock, J. S. (2005). Teaching ESL composition: Purpose, process, and practice (2nd ed.). Mahwah, NJ: Lawrence Erlbaum. Harmer, J. (2007). The Practice of English Language Teaching. Fourth Edition, UK: Cambridge. Jacobs, G. M., Curtis, A., Braine, G., & Huang, S. Y. (1998). Feedback on student writing: Taking the middle path. Journal of Second Language Writing, 7(3), 307-317. Jacobs, H., Zinkgraf, S., Wormuth, D., Hartfiel, V. F., & Hughey, J. (1981). Testing ESLComposition: A practical approach. Rowley, MA: Newbury House. Lee, I. (2003). L2 writing teachers’ perspectives, practices and problems regarding errorfeedback. Assessment Writing, 8, 216-237. Keh, C. L. (1990). Feedback in the writing process: A model and methods for implementation.ELT Journal, 44(4), 294-304. Lee, I. (2008). Understanding teachers’ written feedback practices in Hong Kong secondaryclassrooms. Journal of Second Language Writing, 17, 69-85. Lyster, R., & Ranta, L. (1997). Corrective feedback and learner uptake: Negotiation of form incommunicative classrooms. Studies in Second Language Acquisition, 20, 37-66. Merrill, D. M. (1994). Instructional design theory. Englewood Cliffs, NJ: EducationalTechnology Publications. Merrill, D. M. (2002). Instructional strategies and learning styles: Which takes precedence?In R. A. Reiser & J. V. Dempsey (Eds.), Trends and issues in instructional design andtechnology (99-106). Upper Saddle River, NJ: Pearson Education Inc. Nunan, D. (. (2003). Practice English Language Teaching. New York: Mc. Graw Hill Education. Othman, N.B. (2005). Feedback Lesson on Writing Assessment with Four Different Scoring Strategies. Malaysia: Pendidikan Sultan Idris University. Purnawarman, P. 2011. Impacts of Different Types of Teacher Corrective Feedback in Reducing Grammatical Errors on ESL/EFL Students’ Writing. Virginia: Polytechnic Institute and State University. Randolph, T & Lea, K. (2010).A study of Teacher Feedback in Small Groups with Weekly Writing Assignments. Unpublished, Ed.D. Dissertation, Trevecca Nazarene University, 3413061. Sujoko. 1989. Error Analysis. Surakarta: Sebelas Maret University Press. Taken from http://www.whitesmoke.com/the-stages-of-writing, Retrived July 26, 2013 at 12.20.p.m.